2022
DOI: 10.3390/biomedicines10102491
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification: In Vitro Models under the Magnifying Glass

Abstract: Vascular calcification is a systemic disease contributing to cardiovascular morbidity and mortality. The pathophysiology of vascular calcification involves calcium salt deposition by vascular smooth muscle cells that exhibit an osteoblast-like phenotype. Multiple conditions drive the phenotypic switch and calcium deposition in the vascular wall; however, the exact molecular mechanisms and the connection between vascular smooth muscle cells and other cell types are not fully elucidated. In this hazy landscape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…In general, there is a traditional view of the EC phenomenon as a cellular degenerative, passive process and a newer view as an active, proactive process mediated by cellular metabolism [45]. The most widely used experimental system for CVC is the combination of primary cultures of arterial smooth muscle or valve stromal cells with high concentrations of phosphoric acid [19]. The above-mentioned cell death by high concentrations of phosphate inevitably leads to the loss of cellular metabolic systems, and CaP-ppt formation was explained as a physicochemical reaction associated with the alkalinization of the medium pH by high concentrations (44 mM) of sodium bicarbonate in DMEM culture medium [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, there is a traditional view of the EC phenomenon as a cellular degenerative, passive process and a newer view as an active, proactive process mediated by cellular metabolism [45]. The most widely used experimental system for CVC is the combination of primary cultures of arterial smooth muscle or valve stromal cells with high concentrations of phosphoric acid [19]. The above-mentioned cell death by high concentrations of phosphate inevitably leads to the loss of cellular metabolic systems, and CaP-ppt formation was explained as a physicochemical reaction associated with the alkalinization of the medium pH by high concentrations (44 mM) of sodium bicarbonate in DMEM culture medium [26].…”
Section: Discussionmentioning
confidence: 99%
“…This interesting observation of materials balance was first obtained with the use of CJ cells. In other words, osteoblasts [12], vascular smooth muscle cells [19], and cardiac valve stromal cells [20] all require medium changes every 2 to 3 days during culture, making it difficult to obtain accurate material balance data in the open systems. On the other hand, CJ cells can be cultured for a long period of time without medium change in the closed system, which enables accurate tracking of material balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that vesicles derived from dying cells can concentrate calcium and act as nucleating structures for the crystallization of calcium salts. 49,50 Calcium deposits were also found around dead cells in osteogenic culture. 51 Furthermore, mitochondrial calcium overload is common in pyroptotic cells.…”
Section: Studies Of Interorgan Communications Have Shown the Existenc...mentioning
confidence: 99%
“…Although VC is a pathological process related to aging (Pescatore et al, 2019), many other chronic diseases, such as atherosclerosis, diabetes mellitus, hypertension, and chronic kidney disease, are closely associated with VC occurrence (Palit and Kendrick, 2014;Nicoll et al, 2016;Grootaert et al, 2018;Giha et al, 2022). Multiple mechanisms have been proposed to explain the calcification within the vessel wall, including the osteogenic differentiation of vascular smooth muscle cells (VSMCs) (Ceccherini et al, 2022). In healthy vessels, these contracting cells remain quiescent, regulating the vascular tone and blood pressure.…”
Section: Introductionmentioning
confidence: 99%